Produção de enzimas pelo cocultivo de fungos filamentosos por fermentação em estado sólido e aplicação do meio integral na sacarificação da biomassa para obtenção de etanol celulósico - Maehara, Larissa (2016)
The use of a simplified consolidated bioprocess for the conversion of biomass using enzymes produced in-house (integrated into the process of converting lignocellulosic biomass) may enable significant increases in the production of bioethanol, without the need for expansion of cultivated area. With this motivation, the present work had as objective the study of the steps of production of (hemi)cellulases by solid-state fermentation (SSF) and the use of whole fermentation medium (WFM) for saccharification of biomass and subsequent alcoholic fermentation within the context of a consolidated bioprocess for the 2G ethanol production. To this end, firstly, the selection of the cultivation conditions for the production of enzymes directly using the sugarcane bagasse pretreated by steam explosion (SEB) as SSF substrate was studied. Thus, different fungi were cultivated in isolation and in co-cultivation, including the study of the use of wheat bran and lactose as inducers in the production of enzymes. In order to optimize the enzymatic hydrolysis (EH) step with the WFM from SSF, it was evaluated the influence of the operating parameters and the use of soy protein, Tween 80, PEG 1500 and bovine serum albumin (BSA) as additives. Finally, the alcoholic fermentation step was performed for the selected condition for the overall validation of this bioprocess. The results obtained in the conditions which maximize the production of enzymes, using SEB as substrate, were: addition of lactose at 0.075 g/g of substrate and wheat bran in the mass ratio 1:1 relative to the substrate, which led to an increase of activity of 73% for beta-glucosidase, 67% for endoglucanase, and 72% for xylanase, compared to the control condition using SEB as the substrate, without the presence of lactose or wheat bran. Cultivations under SSF followed by the EH step with the WFM showed that the co-cultivation were, in most cases, better in the conversion of SEB into fermentable sugars. The co-cultivation that presented the best result when compared to the best-isolated cultivation of Aspergillus niger was the Trichoderma reesei with Aspergillus oryzae, which has promoted an increase of 47% in the glucose production. The evaluation of operating parameters (pH, temperature and stirring) during the enzymatic hydrolysis step with the WFM from SSF showed that the saccharification process performed under the condition of pH 4.8, 200 RPM and 50 °C presented the best conversion of lignocellulosic biomass. This operational condition is the same already used in the conventional process of enzymatic hydrolysis with commercial extract enzymes. The addition of additives (soy protein and Tween 80) improved the saccharification process, whereas the addition of soy protein (0.5% w/v) lead to a 50% increase in glucose release. The alcoholic fermentation carried out for validating the overall integration process at the best condition of cultivation /hydrolysis gave a yield of 83.5% of the theoretical yield and volumetric productivity of ethanol (QP) 4.77 g/L.h. These results show that all process steps can be performed sequentially in the same reactor, thus denoting the proposed consolidated bioprocess.